Một số vấn đề lí luận về huy động nguồn lực giáo dục trong tổ chức hoạt động trải nghiệm, hướng nghiệp ở trường trung học - Nguyễn, Thị Ngọc (Tạp chí Giáo dục, 2024)
The 2018 general education program for secondary schools identifies experiential and vocational activities as mandatory educational activities. This is an educational activity with characteristics such as open content with rich topics; diverse organizational methods in different educational environments. Therefore, this process requires organization with the participation of educational forces inside and outside the school and needs to mobilize many other resources such as financial, material and information resources. Based on analysis, synthesis, and comparison of research related to the process of organizing experiential and career guidance activities in high schools. The article presents theoretical issues about mobilizing and synthesizing resources to organize experiential and career guidance activities in schools such as: principles, goals, content and methods of resource mobilization. The research results will help administrators and teachers at secondary schools apply it to synchronously mobilize and coordinate resources to organize quality experiential and career guidance activities in schools, thereby contribute to improving the quality of comprehensive education for students.